The effect of monetary policy on the private sector investment in Morocco: VECM approach - Jalal, BRHOURI; Zineb, EL IDRISSI; Mohamed, OUDRAR; Hajar, Tabyaoui; AMINE, Nabil BOUAYAD; Mohamed, AIT OUDRA (Edelweiss Applied Science and Technology, 2024)
This paper investigates the impact of monetary policy on private investment in Morocco from 2000 to 2023, focusing on both short- and long-term effects of key variables such as interest rates, money supply, and exchange rates. Using a Vector Error Correction Model (VECM), the analysis reveals that, in the short term, economic growth is the primary driver of private investment, while liquidity plays a supportive role. In the long term, GDP growth, foreign direct investment (FDI), and macroeconomic stability are crucial stimulators, whereas tax burden and interest rates hinder investment. Surprisingly, money supply negatively impacts investment, suggesting inefficiencies in resource allocation. The findings highlight the importance of stabilizing exchange rates, maintaining moderate inflation, and reducing tax burdens to foster a favorable investment climate. Policymakers are encouraged to adopt fiscal reforms, optimize monetary tools, and improve financial market efficiency to channel resources into productive investments and drive sustainable economic growth.